Green Human Resource Management in Conjunction with the Sustainability of Corporate Environments - Ghimire, S; Mishra, AK; Bhaumik, A (Journal of Advanced Research in HR and Organizational Management, 2022)
Recently, there has been an experienced increase in the level of awareness among business groups about the relevance of becoming green and implementing different approaches for environmental management. Provisions such as green personnel, green professions, green occupations are becoming more commonplace in the present world. The business world is becoming more globalized, concurrently, the business is undergoing a transition from an outdated financial structure to a contemporary capacity-based economy that is green to investigate the environmentally responsible parts of the organization’s operations. The “green revolution” also known as “going green”, “ecological protection” or “environmental sustainability”, “sustainable standard of living”, “caring for our earth”, a number of other similar concepts, have evolved into natural phenomena that are easily visible in our day-to-day lives. At the present time, Green Human Resource Management, also known as GHRM, has developed into a vital business strategy for big corporations. This is the case in companies where the Human Resource Departments take an active role in making the workplace more environmentally friendly. This paper focuses primarily on the numerous green human resource policies and practices with corporate environmental sustainability and data obtained from secondary accessible sources. It provides an explanation of the essential functions that next-level thinking of a new population of people plays in terms of green technology and knowledge. In addition to this, the study contributes to the existing body of literature by addressing the trajectory of the development of various environmentally green functions. In conclusion, the paper presents a few potentially fruitful HR initiatives that green businesses should use to rescue both the environment and people. How to cite this article: Ghimire S, Mishra AK, Bhaumik A. Green Human Resource Management in Conjunction with the Sustainability of Corporate Environments. J Adv Res HR Organ Mgmt 2022; 9(3&4): 6-11. DOI: https://doi.org/10.24321/2454.3268.202202